A protocol for single‐source dual‐pulse stimulated emission depletion setup with Bessel modulation. Issue 2 (6th September 2021) - Xu, Xinzhu; Zhao, Kun; Ren, Wei; Wu, Zhaoyang; Yu, Wentao; Shao, Chendi; Shi, Kebin; Xi, Peng
Abstract: STimulated Emission Depletion (STED) microscopy attains super‐resolution in biological imaging beyond the diffraction limit. Here, we give a concise protocol to construct a dual‐pulse STED setup with one super‐continuum laser. Moreover, a flexible and dismountable Bessel modulation module is introduced for potential 2D‐stack STED imaging. Experiments and notices are introduced in detail, with discussion on some important check‐points for STED, such as detector saturation. Finally, the results validate the system working. Abstract : A STED setup construction protocol is introduced with single source split into dual pulse, serving as excitation and depletion respectively, thus, there is no need to temporally synchronize the two pulses and only temporal delay should be set up, which minimizes the complex of the optical system, and also makes it cost‐effective. The nondiffraction property of Bessel beam bestows potential 2D‐stack STED imaging, hence, a dismountable Bessel modulation is introduced in system. The construction steps consist of setup elements introduction, time delay, polarization control, point spread function alignment, depletion efficiency, Bessel modulation and STED/GB‐STED resolution measurements, and experiment notices including detector saturation are also discussed in detail. Furthermore, we provide the whole customer‐designed Labview program to control sample‐scanning and signal‐capturing for promoting the home‐made STED setups.